Plasma levels of carcinoembryonic antigen in bronchial carcinoma and chronic bronchitis. - Pauwels, R (1975)
The plasma levels of carcinoembryonic antigen were increased in 80% of 49 patients with bronchial carcinoma and in 68% of 25 patients with an acute exacerbation of chronic bronchitis. There was no statistically significant difference between the two groups. A single determination of the plasma carcinoembryonic antigen level has no prognostic value in patients with bronchial carcinoma.